Differences in Rape Acknowledgment and Mental Health Outcomes Across Transgender, Nonbinary, and Cisgender Bisexual Youth - Anderson, RaeAnn E. (Journal of interpersonal violence, 2021)
The purpose of this study was to document the rates of rape acknowledgment (labeling rape as rape rather than using a minimizing label) and the corresponding mental health correlates using the minority stress framework in a unique and vulnerable sample: racially diverse sexual and gender minority young adults. Participants were 245 young adults who identified their sexual orientation as under the bisexual umbrella. A total of 159 of these participants (65.2%) identified their gender identity as nonbinary. All participants completed a series of online questionnaires regarding their sexual victimization history, mental health outcomes (depression, anxiety, and posttraumatic stress disorder [PTSD]), and constructs relevant to minority stress theory (level of outness, internalized bisexual negativity, connection to LGBTQ [lesbian, gay, bisexual, transgender, questioning] community). Rape acknowledgment was significantly greater among gender nonbinary participants (79.9%) than among trans and cisgender male participants (17.9%). Lack of rape acknowledgment was associated with increased anxiety, depression, and PTSD. Outness was significantly associated with greater rape acknowledgment. Despite the highly increased vulnerability for sexual violence among sexual and gender minorities, very little is understood about the mechanisms of this increased vulnerability or their unique needs for recovery. The results of this study strongly suggest the importance of a minority stress framework for understanding this increased vulnerability and for designing sexual violence prevention and recovery interventions for sexual and gender minority populations.